Bioactivities, chemical composition and nutritional value of Cynara cardunculus L. seeds - Petropoulos, Spyridon A.; Fernandes, Ângela; Pereira, Carla; Tzortzakis, Nikos G.; Vaz, Josiana; Soković, Marina; Barros, Lillian; Ferreira, Isabel C. F. R. (My University, 2019)
In the present study, the nutritional value, bioactive properties, and chemical composition of various cardoon (Cynara cardunculus L.) genotypes cultivated in central Greece were investigated. The results demonstrated that Cynara seeds are a good source of fat and protein, while they also contain considerable amounts of K, Mg, and Fe and low amount of Na. Sucrose, oxalic acid, and α-tocopherol were the only free sugar, organic acid, and tocopherol isoform respectively, found among the studied genotypes. The most abundant fatty acids were linoleic, oleic and palmitic acid, while PUFA was the most abundant fatty acid class. All the tested seeds contained only two phenolic compounds, namely 5-O-caffeoylquinic acid and 3,5-O-caffeoylquinic acid, while significant antioxidant activities and cytotoxicity against tumor cell lines and antimicrobial effects were also observed. In conclusion, cardoon seed extracts could be exploited in the food and pharmaceutical industries as alternative sources of natural compounds with bioactive properties.
Keywords: Antimicrobial effects; Antioxidant activity; Cardoon; Cynara cardunculus L.; Cytotoxicity; Globe artichoke; Nutritional value; Phenolic compounds